To the Lighthouse - Woolf, Virginia (Lahore Famous Books, 1927)
From the seemingly trivial postponement of a visit to a nearby lighthouse, author Virginia Woolf constructs a remarkable and moving examination of the complex tensions and allegiances of family life, and the conflict between male and female principles.
Keywords: Married people -- Scotland--Island of Skye -- Lighthouses